Preconditioned wire array Z-pinches driven by a double pulse current generator. (6th June 2018) - Wu, Jian; Lu, Yihan; Sun, Fengju; Li, Xingwen; Jiang, Xiaofeng; Wang, Zhiguo; Zhang, Daoyuan; Qiu, Aici; Lebedev, Sergey
Abstract: Suppression of the core-corona structure and wire ablation in wire array Z-pinches is investigated using a novel double pulse current generator 'Qin-1' facility. The 'Qin-1' facility allows coupling a ∼10 kA 20 ns prepulse generator with a ∼0.8 MA 160 ns main current generator. The tailored prepulse current preheats wires to a gaseous state and the time interval between the prepulse and the main current pulse allows formation of a more uniform mass distribution for the implosion. The implosion of a gasified two aluminum-wire array showed no ablation phase and allowed all array mass to participate in the implosion. The initial perturbations formed from the inhomogeneous ablation were suppressed, however, the magneto Rayleigh–Taylor (MRT) instability during the implosion was still significant and further researches on the generation and development of the MRT instabilities of this gasified wire array are needed.